Crossing the racial line: The fluidity vs. fixedness of racial identity. Issue 5 (4th July 2021) - Small, Payton A.; Major, Brenda
ABSTRACT: Five studies investigated perceptions of individuals whose identity claims violate societal ascriptions of group membership. Studies 1–3 showed that perceivers dislike targets whose claimed race/ethnicity does not match either of their parent's racial/ethnic ancestry, delegitimize their identity claims, and deny their claimed identity relative to targets whose claimed race/ethnicity matches at least one of their parents' racie/ethnicity backgrounds. Study 4 showed that mismatched religious identities are not similarly devalued, suggesting that perceived misrepresentation of racial/ethnic identity holds special significance as a violation of social norms. Study 5 found that racial essentialism was associated with increased disparagement of targets with two White parents who claim a Black identity, but not of targets with two Black parents who claim a White identity.